Quality of methods and reporting in association studies of chronic periodontitis and IL1A−889 and IL1B+3953/4 SNPs: A systematic review. (15th April 2019) - Citterio, Filippo; Romano, Federica; Ferrarotti, Francesco; Gualini, Giacomo; Aimetti, Mario
Abstract : Objective: The aim of this systematic review was to evaluate the quality of reporting and methodology in genetic association studies between IL1A −889 and IL1B +3954 polymorphisms and chronic periodontitis. Background: Evidence provided by periodontal research on genetic risk factors is of uttermost importance in clinical practice as a possible diagnostic and prognostic tool for periodontitis. Inadequate reporting of results as well as high risk of bias due to methodological inconsistency hampers the integration of evidence in terms of clinical applicability. Methods: This review includes case‐control studies in humans published between 1997 and July 2017. Searching was conducted through MEDLINE, EMBASE, and search handing. Specific scoring systems have been developed to evaluate the quality of methods and reporting. Each article was scored according to its adequacy, and then, the total number and the percentage of items positively qualified for both methods and reporting were calculated. The quality of methods in studies scoring 0‐6, 7‐12, and 13‐16 was, respectively, considered poor, moderate, and good. For reporting, scores of 0‐9, 10‐18, and 19‐26 were deemed of poor, moderate, and good quality, respectively. Pearson's correlation coefficient was calculated to explore the correlation between the year of publication and the quality in terms of methods and reporting. Results: From the 531 screened studies, 52 met the inclusion criteria and were thus included in the study. The quality of methods and reporting of published genetic association papers on IL1 and chronic periodontitis is moderate. On a scale from 0 to 16, the mean score for methods of the reviewed studies was 8.19 ± 1.93. The items more frequently considered inadequate concerned the handling of confounders in statistical analysis, especially oral hygiene habits, socioeconomic status, subgingival colonization of specific periodontal pathogens, and stress. A significant positive correlation was found between the year of publication and the quality scores in terms of method ( r = 0.401, P = 0.003). In terms of reporting, the mean score was 14.83 ± 3.04 on a scale from 0 to 26 and it was considered overall moderate. No statistically significant correlation was found between the year of publication and the quality of reporting ( P = 0.266). Conclusions: The association between IL1A −889 and IL1B +3954 polymorphisms and chronic periodontitis is questionable due to methodological inconsistency. Evidence arising from meta‐analysis is unreliable due to high risk of bias and moderate quality in terms of reporting.